Perkembangan Organisasi Penyelenggara Lembaga Pendidikan Islam Yayasan Al-Ma’ruf di Daerah Minoritas Muslim - Dina Delda Sari Pulungan; Jumari Jumari; Imam Muhayat (JIE (Journal of Islamic Education), 2022)
This research is motivated by the lack of complete information both from books and study texts about the problems and organizational development of Islamic educational institutions in Muslim minority areas, especially in Bali, namely the Al-Ma'ruf Foundation. The purpose of this research is to find out the development of the organization providing Islamic education at the Al-Ma'ruf Foundation in the Muslim minority area of Denpasar in 2004–2021. This study used a qualitative descriptive method, collecting data through observation, interviews, and documentation. The results of the study show an overview of the research location to prove the awareness, compliance, and thoroughness of internal and external foundations towards the condition of the Muslim minority. Apart from experiencing such a rapid evolution, the Al-Ma'ruf Denpasar Foundation has also experienced stagnation and involution in some of its activities, as well as the obstacles faced by the foundation, namely the provision of land and buildings, approval from the environment, as well as the readiness of human resources who are professional, qualified, and competent. The foundation's solution is to rent land contracts, support funds from the foundation's business, persuasive approaches to the surrounding community and related officials, and ask for the help of experts, including teachers and staff from Java as the most prominent Muslim area.